Case Report: Favorable outcome in a patient with simultaneous dengue meningoencephalitis and Wernicke’s thiamine deficiency - Saket Satyasham Toshniwal; Jiwan S. Kinkar; Sourya Acharya; Sunil Kumar (Frontiers in Medicine)
This case report describes the case of a 35-year-old man with a history of chronic binge drinking who presented with fever, associated confused state of mind, and symptoms indicative of acute alcohol withdrawal, including tremors and agitation. Routine investigations revealed pancytopenia and a positive dengue NS1 antigen test, confirming a diagnosis of dengue fever. Neurological examination revealed abnormalities, such as nystagmus, ophthalmoplegia, and altered mental status, which raised the initial suspicion of an alternative diagnosis of Wernicke’s encephalopathy (WE). Magnetic resonance imaging (MRI) revealed bilateral thalamic hyperintensities and meningeal enhancement, while the positive dengue status revealed a rare manifestation of dengue meningoencephalitis. However, owing to the patient’s history of chronic alcoholism, WE could not be completely ruled out. The diagnostic challenge in distinguishing between WE and dengue-associated neurological complications is highlighted by the overlapping symptoms in this case. Furthermore, early administration of thiamine played a crucial role in managing the patient’s condition, highlighting the importance of timely intervention in such complex cases marked by diagnostic uncertainties.